Measurement of the cross section for top quark pair production in association with a W or Z boson in proton-proton collisions at $\sqrt{s} =$ 13 TeV - CMS collaboration (2258 authors) (2017)
A measurement is performed of the cross section of top quark pair production in association with a W or Z boson using proton-proton collisions at a center-of-mass energy of 13 TeV at the LHC. The data sample corresponds to an integrated luminosity of 35.9 fb$^{-1}$, collected by the CMS experiment in 2016. The measurement is performed in the same-sign dilepton, three- and four-lepton final states. The production cross sections are measured to be $σ(t\overline{t}W)= 0.77 ^{+0.12}_{-0.11}\text{(stat)} ^{+0.13}_{-0.12}\text{(syst)}$ pb and $σ(t\overline{t}Z) = 0.99 ^{+0.09}_{-0.08}\text{(stat)} ^{+0.12}_{-0.10}\text{(syst)}$ pb. The expected (observed) signal significance for the $t\overline{t}W$ production in same-sign dilepton channel is found to be 4.5 (5.3) standard deviations, while for the $t\overline{t}Z$ production in three- and four-lepton channels both the expected and the observed significances are found to be in excess of 5 standard deviations. The results are in agreement with the standard model predictions and are used to constrain the Wilson coefficients for eight dimension-six operators describing new interactions that would modify $t\overline{t}W$ and $t\overline{t}Z$ production.